PENGARUH PEMBERIAN MIKORIZA DAN BAHAN ORGANIK TERHADAP PERTUMBUHAN BIBIT KOPI (Coffea sp.) - Fani Ardiani; Herry Wirianata; Pauliz Budi Hastuti (AGROISTA : Jurnal Agroteknologi, 2018)
The purpose of this study was to find out the effect of mycorrhizae and organic materials on the coffee seedlings growth. The experimental design was the Complete Group Randomized Design by using factorial pattern with two factors. The first factor was the dose of mycorrhizal with 3 levels; namely with no mycorrhizae, 5 g / polybag, and 10 g / polybag. The second factor was the type of organic materials with 4 factors; namely with no organic material, compost, lamtoro green manure, and vermicompost. Each combination treatment has 6 replication. The results of the experiments showed that mycorrhizal fungi did not provide the real interactions for almost all observed parameters, except for seedling height, and dry weight of coffee seedlings. Application of 5 grams of mycorrhizae on the media mixed with lamtoro leaves has produced the best plant height of 22.27 cm, while the best parameters for stem dry weight were in the giving of 10 grams of mycorrhizal in media mixed with lamtoro leaves, which was 1.58 grams . The results of the experiments also showed that the giving of various kinds of organic materials had a good influence on the number of leaves, number of roots, wet weight of roots, wet weight of leaves, dry weight of roots, and dry weight of leaves. In the parameters of the number of leaves, number of roots, wet weight of roots, and dry weight of roots; the best results were coffee seedlings planted in soil media (without organic material addition). While the treatment of planting media with lamtoro leaves gave the best results on wet weight of stems (2.97 g), wet weight of leaves (10.79 g), and dry weight of leaves (3.13 g). Keywords: mycorrhizae, organic materials, the coffee seedlings growth